Nutrients uptake study of castor hybrids at different physiological growth stages under North Gujarat Agro-Climatic Conditions: N-UPTAKE STUDY OF CASTOR AT PHYSIOLOGICAL GROWTH STAGES UNDER NORTH GUJARAT - PURVIKUMARI T PATEL,; S K SHAH,; A M PATEL,; KHUSHBUBEN K PATEL,; JINAL A PATEL, (Journal of Oilseeds Research, 2025)
A field experiment was conducted in split plot design with three replications to assess different growth parameters, nutrient content and uptake by different castor hybrids, at sandy loam soils of Castor-Mustard Research Station, Sardarkrushinagar, Gujarat. Fifteen treatment combinations include: three hybrids as main plots, five levels of growth stages as sub plots. The observations were recorded on five tagged plants in respective treatment plots. Growth, yield and quality parameters of castor viz., number of leaves per plant (62), fresh and dry weight of leaves (347.7 g and 55.7 g/plant respectively), fresh and dry weight of stem (909.2 g and 436.9 g respectively) were significantly maximum with hybrid GCH- 9 at growth stage G3 (Harvesting of first order spike) except fresh and dry weight of stem recorded at growth stage G4 (Harvesting of second order spikes). Number of spikes per plant (11), number of capsules per spike (87), length of spike (81.2), test weight (34.0 g), yield (3217 kg/ha), oil content (50.8 %) were recorded significantly maximum with hybrid GCH 8 at growth stage G4 (Harvesting of second order spikes). Fresh weight (2049.3 g/plant) of spikes was also significantly affected by hybrid GCH -7. Significantly higher nutrients content of N, P, K and S recorded in hybrid GCH -8. Significantly higher nutrient uptake of N by leaves recorded at growth stage G4 (Harvesting of second order spikes) while, P, K and S recorded at growth stage G3 (Harvesting of first order spike). Significantly higher nutrients content of N, P, K and S in stem recorded at growth stage G4 (Harvesting of second order spikes) in hybrid GCH- 8. Significantly higher nutrients uptake of N and K by castor stem recorded from GCH- 9 hybrid, while P and S respectively recorded in GCH-8 and GCH-7 at growth stage G4.